(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Gender inequality in teaching profession remains as unsettling concern in education system. Gender composition of teachers is reported imbalanced, in which female teachers take up 71% of the total number of teachers in Indonesia and only 29% are the male teachers. Higher education institutions must consider gender perspectives in preparing their graduate employability, specifically in teacher education discipline, in order to improve the education quality. This study aims to determine gender differences in graduate employability of math teacher education students in public and private universities. A total of 237 final year math teacher education students in Indonesia participated, comprised of 133 from public universities and 104 from private universities. Data was obtained using Career EDGE Employability Development Profile developed by Pool and Sewell (2015). No significant difference was found in graduate employability between male math teacher education students in public universities and private universities (p > .05). In contrast, there was a significant difference in graduate employability between female math teacher education students in public universities and private universities (p < .05). The result implies that future female math teacher education students are better to continue their undergraduate program in public universities in order to acquire higher graduate employability. This study also suggests to carry out an intervention particularly for male math teachers in order to increase men’s participation in mathematic teaching profession.